Analysis of Communication Patterns in Facing the Gap Generation - Nethanya, Thalia; Setiawati, Sri Dewi (Program Studi Ilmu Komunikasi FBIK Unissula, 2025)
In implementing communication within a company, intergenerational communication challenges often lead to differences in perspectives, actions, habits, and attitudes. The disparity in viewpoints between senior and junior employees can trigger conflicts. However, PT. PXX is a company that does not exhibit significant generational gaps compared to other companies. The generational gap (Gap Generation) has specific impacts within the company, such as seniors often feeling more knowledgeable than juniors, causing juniors to hesitate in expressing their opinions as they feel less involved. This study aims to understand the message construction formed by employees to avoid the Gap Generation, the use of communication media, and the role of leaders in addressing the Gap Generation. The research method used is qualitative with a case study approach. The study involves two internal employees of PT. PXX, one communication expert lecturer, and one supporting informant from the internal public relations of PT. PXX. The results of the study indicate that PT. PXX has a relaxed and flexible communication culture between superiors and subordinates, creating more informal and open interactions, allowing employees to feel comfortable expressing ideas, opinions, and concerns without fear of negative consequences.